الاشتقاق والبُنَى المعروفة عند علماء العربية (الكلمة، الجملة، النص، الخطاب) - Syeda Afshan Qasim; Muhammad Bashir (Pakistan Journal of Islamic Research)
All languages are initially acquiring derivation in its all forms and formations to tend to contextual based multicolored meanings.  Derivation comes at first to all language creator sources. It is differing from language to other language. The language, which it has been properly articulated and written in, is Arabic. There is no doubt to declare Arabic being a supreme language in this regard. All semantic and non-semantic languages have been affected by Arabic and vice versa. Derivation falls in itself in four segments; Word, Sentence, Text and Discourse. All these four Diasporas are common in all languages but they are having several differences too. For instance, Arabic has different formation of word and sentence than other languages as it is having different concept of text and discourse than almost all other languages, in particular, Indo-European languages. Along with all these differences there are many similarities too. Derivation is a wonderful classification in Arabic language. Many modern linguistics based concepts that are narrated and uttered by linguists bear no comparison with Arabic Diaspora: This paper intends to classify how Arabic Derivation seems similar to them and where it differs from them as well.